PERFORMANCE AND TRAINING PROGRAM CHARACTERISTICS IN ELITE YUNIOR FEMALE ROLLER SKIER FROM 2021 SEASON: A CASE REPORT - Jakovics, Marcis; Pontaga, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The purpose was to evaluate the training program, body mass composition, aerobic performance laboratory and field test results, blood hormone concentration in elite junior female roller skier in successful competition season. Methods. Totally 206 training sessions (278 training hours) were analysed during six months (from April till September). Athlete wight and body fat changes were monitored, laboratory tests on a treadmill and field tests were performed and concentration of hormones in the blood was detected. Results. A polarised training intensity distribution was observed. The highest volume of training workloads (70 training hours per month) was achieved in the last month before start of World cup season, this change corelated with change in blood testosterone levels. Heart rate decreased by 7.51% at the anaerobic threshold load intensity and by 10.1% at lower intensity loads. Peak oxygen uptake (VO2max) of 49 ml/kg/min was reached in laboratory test. Increase of lean body mass by 2.4 kg was observed. The progress in 3000m running race time was detected from 14:30 minutes in the beginning of April to 13:16 minutes in June. Conclusion. VO2max in junior elite female roller skier is low in comparison with cross-country skiers, but the training workload intensity and volume are comparable with skiers. This research shows insight in top junior level female roller-skiers physiology and training, but specific values determining the success of this athlete are still to be determined if compared to traditional cross-country skier.